Analisis faktor tentang psychological distress pada tenaga kesehatan - Novianti, Hernia; Ichwansyah, Fahmi; Marthoenis, Marthoenis; Abdullah, Asnawi; Zakaria, Radiah (Holistik Jurnal Kesehatan, 2025)
Background: Healthcare workers face various challenges in carrying out their duties, which can impact their psychological condition. Work pressure, demands for professionalism, and situations in the healthcare service environment can affect their mental well-being. This condition requires attention, as it may influence the quality of care provided. Purpose: To analyze the factors associated with psychological distress among healthcare workers. Method: This quantitative study employed a cross-sectional design. The research was conducted in January in Central Aceh District. A total of 300 healthcare workers—including nurses, midwives, environmental health workers, and epidemiologists—participated in this study. The sampling technique used was cluster random sampling. Data were collected using a questionnaire distributed via Google Form. Data analysis was carried out using univariate, bivariate, and multivariate approaches through logistic regression and multiple logistic regression test. Results: Statistical analysis showed that low social support (OR = 10.07; p = 0.037), heavy workload (OR = 30.16; p = 0.0001), severe work fatigue (OR = 159.5; p = 0.0001), shorter duration of work (OR = 10.69; p = 0.0001), and the midwife profession (OR = 3.38; p = 0.007) were significantly associated with psychological distress. The most influential factors were severe work fatigue (AOR = 51.84; p = 0.040), longer duration of work (AOR = 59.83; p = 0.0001), and the profession of nurse (AOR = 8.12; p = 0.031) and midwife (AOR = 9.43; p = 0.031). Conclusion: The variables of social support, workload, work fatigue, length of service, and profession were significantly associated with psychological distress among healthcare workers.   Keywords: Healthcare Workers; Psychological Distress; Workload.   Pendahuluan: Tenaga kesehatan menghadapi berbagai tantangan dalam menjalankan tugasnya yang dapat berdampak pada kondisi psikologis tenaga kesehatan. Tekanan kerja, tuntutan profesionalisme, dan situasi di lingkungan pelayanan kesehatan dapat memengaruhi kesejahteraan mental tenaga kesehatan. Kondisi ini perlu mendapatkan perhatian, karena dapat berpengaruh terhadap kualitas pelayanan yang diberikan. Tujuan: Untuk menganailis faktor yang berhubungan dengan psychological distress pada tenaga kesehatan. Metode: Penelitian kuantitatif menggunakan desain cross-sectional. Penelitian dilaksanakan pada bulan Januari di Kabupaten Aceh Tengah. Sebanyak 300 tenaga kesehatan yang terdiri dari perawat, bidan, tenaga kesehatan lingkungan, dan epidemiologi menjadi partisipan dalam penelitian ini. Pemilihan sampel menggunakan teknik cluster random sampling. Alat pengumpulan data menggunakan angket yang disebarkan melalui Google Form. Analisis data dilakukan secara univariat, bivariat, dan multivariat menggunakan uji regresi logistik dan regresi logistik berganda. Hasil: Analisis statistik menunjukkan bahwa dukungan sosial rendah (OR = 10,07; p = 0,037), beban kerja berat (OR = 30,16; p = 0,0001), kelelahan kerja berat (OR = 159,5; p = 0,0001), masa kerja baru (OR = 10,69; p = 0,0001), dan profesi bidan (OR = 3,38; p = 0,007) memiliki hubungan yang signifikan dengan psychological distress. Faktor yang paling berpengaruh adalah kelelahan kerja berat (AOR = 51,84; p = 0,040), masa kerja lama (AOR = 59,83; p = 0,0001), serta profesi perawat (AOR = 8,12; p = 0,031) dan bidan (AOR = 9,43; p = 0,031). Simpulan: Variabel dukungan sosial, beban kerja, kelelahan kerja, masa kerja, dan profesi memiliki hubungan yang signifikan dengan psychological distress pada tenaga kesehatan.   Kata Kunci: Beban Kerja; Psychological Distress; Tenaga Kesehatan.